Work Facilities Redesign Based on Subjective Complaints of Eggroll Snacks Workers - Tri Anggoro Istianto; Retno Rusdjijati; Oesman Raliby Al-Manan (Urecol Journal. Part E: Engineering, 2022)
Eggroll snack workers often experienced subjective complaints on the waist, back, lower neck and upper neck, as well as the right forearm. This is caused by awkward work attitudes such as bending, looking down, standing and sitting for too long which is done repeatedly. This awkward work attitude is caused by non-ergonomic work facilities, such as a work desk that is too high or a work chair that is too short. So that subjective complaints experienced by workers can be minimized, it is proposed to redesign the work facilities of the eggroll snack production process based on ergonomic principles. The redesign includes 1) adding a support to the dough container with a height of 82.6 cm and can be raised and lowered; 2) redesign of the work table with a height of 64.5 cm, a width of 61 cm, a forward arm reach of 45.4 cm, and a redesign of a chair with a height of 70 cm and a side reach of 46.7 cm; and 3) the addition of product packaging supports with a height of 50.8 cm, chair height of 40 cm, and reach of the hands forward of 38.8 cm. The redesigned work facility is expected to be followed up by business actors, so that workers feel comfortable working, free from subjective complaints.